Analysis of the Number of Malaria Sufferers in Wajo Regency Based on Districts in 2017-2018 - Asnita Sari; Andi Anindyah Artanty (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Maternal and child health is a key indicator used to measure population health status and to assess the success of health sector development. West Sulawesi Province, as part of Eastern Indonesia, continues to face substantial challenges in reducing maternal and infant mortality rates. These challenges are influenced by multiple factors, including geographical barriers, limited accessibility to health services, unequal distribution of health workers, and socio-cultural conditions that affect health-seeking behavior. Consequently, disparities in maternal and newborn mortality remain evident across the region. Objective: This study aims to describe the distribution of maternal and infant mortality rates in West Sulawesi Province during the period 2017–2020, using secondary data obtained from the West Sulawesi Provincial Health Profile. Method: A quantitative descriptive approach was employed by analyzing secondary data sourced from the West Sulawesi Provincial Health Profile. The data analyzed consisted of annual records of maternal and infant deaths. Data analysis was conducted by organizing the information into tables and graphical displays, followed by narrative interpretation to identify patterns and trends over time. Results: The findings indicate fluctuations in both maternal and infant mortality rates between 2017 and 2020. Infant mortality rates showed a decline in certain years, while maternal mortality rates remained relatively stable but at persistently high levels. Geographic constraints, limited availability of health facilities, and socio-cultural factors are considered major contributors to these trends. Conclusion: The distribution of maternal and infant mortality rates in West Sulawesi Province highlights the urgent need to strengthen maternal and newborn health services. Improving referral systems, expanding access to health care in remote areas, and implementing community-based and evidence-based policies are essential to achieving sustainable maternal and child health outcomes.